Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.11114/jets.v5i9.2584
|View full text |Cite
|
Sign up to set email alerts
|

Examining Students’ Opinions about STEAM Activities

Abstract: The purpose of this study is to determine the opinions of students about STEAM activities. This qualitative study was conducted on the with 7 th grade students (n=37) who are studying at a public school in Istanbul. A purposeful sampling was used in this study. Nine STEAM activities were used while teaching Force and Energy unit. An evaluation form which is composed of open-ended questions was used as a data collection instrument at the end of the teaching process. The responses provided by students for the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Since the STEM implementations in our study were at the university level, the PSSTs may have thought that implementing a STEM activity at the primary education level would also require such metacognitive and psychomotor skills. In their study, Ozkan and Topsakal (2017) found that PSSTs also had challenges in the stages requiring psychomotor skills in the STEM education process. Similarly, educators state that students' weak skills are one of the most significant barriers to using alternative educational approaches (Dancy & Henderson, 2008).…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 98%
“…Since the STEM implementations in our study were at the university level, the PSSTs may have thought that implementing a STEM activity at the primary education level would also require such metacognitive and psychomotor skills. In their study, Ozkan and Topsakal (2017) found that PSSTs also had challenges in the stages requiring psychomotor skills in the STEM education process. Similarly, educators state that students' weak skills are one of the most significant barriers to using alternative educational approaches (Dancy & Henderson, 2008).…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 98%
“…Bu bağlamda, araştırmanın da geliştirmiş olduğu sanatsal kazanımlar değerlidir. STEM'in evrilmiş hali olarak kabul edilebilecek STEAM yaklaşımı alanında yapılan çalışmalarda da bu disiplinlere yönelik olumlu değişimlerin meydana geldiği tespit edilmiştir (Kim, Nam & Lee, 2014;Kim, Ko, Han & Hong, 2014;Kong & Ji, 2014;Kong & Huo, 2014;Özkan & Umdu-Topsakal, 2017;Gülhan & Şahin, 2018a;Gülhan & Şahin 2018b). STEAM fen ve matematik alanında köklenen disiplinlerin özgünlükteki etkililiğinin sağlanabilmesi için çok önemlidir (Bequette & Bequette, 2012).…”
Section: Discussionunclassified
“…Bilimsel etik, sosyal gelişim, liderlik ve etkili iletişim yeteneğinin de sürece dâhil olduğu yoğun bir yetenek geliştirme tasarımını ifade etmektedir.Alan yazında STEM disiplinlerine Sanat'ın entegrasyonuna yönelik çalışmalar bulunmaktadır ve bu çalışmalar incelendiğinde disiplinlerin bilgi, algı, tutum ve yaratıcılık üzerine etkisinin incelendiği görülmektedir(Yakman, 2008;Kwona, Namb & Lee, 2011;Sousa & Pilecki, 2013; Jin, Chong & Cho, 2013;Kim, Ko, Han & Hong, 2014;Henriksen, 2014;Jeong & Kim, 2015;Gülhan & Şahin, 2016;Rolling, 2016;Sochacka, Guyotte & Walther, 2016;Ayvacı & Ayaydın, 2017;Cook, Bush & Cox, 2017;Cook & Bush, 2018). Ulusal çalışmalarımız incelendiğinde ise STEAM ile ilgili yapılan çalışma sayısının sınırlı olduğu görülmektedir(Batı, Çalışkan & Yetişir, 2017;Özkan & Umdu-Topsakal, 2017;Gülhan & Şahin, 2018a;Gülhan & Şahin, 2018b). STEAM çalışmalarının sadece fen ve matematik alanındaki araştırmacılar tarafından çalışılmasının yanı sıra bu disiplinlerin entegrasyonuna örnek teşkil edilebilecek uygulamaların çerçevesinin de net olarak belirlenmediği görülmektedir.…”
unclassified
“…Myös aiemmat tutkimukset ovat osoittaneet oppijoiden suhtautuvan STEAM-projekteihin positiivisesti (esim. Julià & Antoli, 2019;Ozkan & Topsakal, 2017;Tunnard & Sharp, 2009).…”
Section: Pohdinta Ja Johtopäätöksetunclassified